# Given: -3x + y = 1. Write the equation in general form ax + by + c = 0.

**Solution:**

The equation given is

-3x + y = 1

We have to write in general form ax + by + c = 0

Let us proceed below,

-3x + y - 1 = 0

Therefore, the equation in general form is -3x + y - 1 = 0.

Example - **Given: 4x + y = 3. Write the equation in general form ax + by + c =0.**

**Solution:**

The equation given is

4x + y = 3

We have to write in general form ax + by + c = 0

So we get

4x + y - 3 = 0

Therefore, the equation in general form is 4x + y - 3 = 0.

## Given: -3x + y = 1. Write the equation in general form ax + by + c = 0.

**Summary:**

Given: -3x + y = 1. The equation in general form ax + by + c = 0 is -3x + y - 1 = 0.